Touch DNA recovery from unfired and fired cartridges: Comparison of swabbing, tape lifting and soaking. (January 2022) - Prasad, Elisha; Hitchcock, Catherine; Raymond, Jennifer; Cole, Andrew; Barash, Mark; McNevin, Dennis; van Oorschot, Roland A.H.
Highlights: Three DNA sampling methods were compared for handled cartridges and fired cases. Swabbing recovered significantly less DNA than tape lifting and soaking. Firing reduced DNA recovery and the numbers of alleles detected. Majority of profiles from unfired tape lifted samples were potentially uploadable. Tape lifting may be a suitable alternative to swabbing cartridges and fired cases. Abstract: Over the recent few years, several DNA collection techniques and methodologies have been published for the recovery of DNA from fired cartridge cases. In this study, swabbing, the DNA collection technique currently used in our jurisdiction (NSW, Australia), was compared with tape lifting and soaking to assess DNA recovery rates, DNA quality and profile quality. Brass .22LR and 9mmP cartridges were used as they are the most commonly encountered in our jurisdiction. The cartridges (n = 107) were loaded into cleaned firearm magazines by three volunteers of unknown shedder status, to mimic routine casework sample types. Half of the handled cartridges were fired whilst the other half were kept unfired. STR genotypes were produced at both 29 and 30 PCR cycles to evaluate which improved handler allele detection. DNA recovery rates showed that swabbing recovered significantly less DNA than tape lifting and soaking. Whilst there were no significant differences between tape lifting and soaking, tape lifting, on average, yielded more DNA than soaking. The calibre of ammunition had no influence on DNA recovery and in line with expectations, firing was found to decrease DNA recovery for all three sampling techniques. Assessment of DNA quality showed no evidence of PCR inhibition in any of the samples for this study. However, degradation indices showed that most samples were slightly to moderately degraded. Fewer handler alleles were detected from both fired tape lifted and soaked cartridges than unfired cartridges. Whilst 30 amplification cycles allowed for the detection of slightly more handler alleles, no statistically significant differences were found between 29 and 30 PCR cycles. Nonetheless, 50% of the profiles from unfired soaked cartridges that were non-uploadable after 29 cycles were uploadable after 30 cycles. Furthermore, 83% of profiles from unfired cartridges that were tape lifted were uploadable onto our jurisdiction's database at both 29 and 30 PCR cycles. All magazine controls, despite cleaning, contained some level of background DNA. Furthermore, increasing the number of PCR cycles to 30 also increased the detection of non-handler alleles in DNA profiles. Our results suggest tape lifting yields more uploadable profiles from unfired and fired cartridge cases than swabbing but also more adventitious (non-handler) alleles. However additional research will be needed to evaluate the full potential of this method.